Synthesized carbon material with semi-organic and aqueous electrolyte for supercapacitor application - Avinash P. Moholkar; Deepak S. Bankar; Parshuram B. Karandikar (Institute of Advanced Engineering and Science, 2022)
The supercapacitor is an evolving technology that has a potential to play a vital role in the today’s electrical energy storage systems. Supercapacitors are dominated by unique properties that can accompany other energy storage strategies due to its functional characteristics - such as quick charge/discharge ability, higher power density, very long cycle life. It results in to improved system efficiency of hybrid electric energy systems with reduced environmental pollution levels. In this paper, efforts are made to fabricate a low cost prototype of supercapacitor using synthesised carbon material obtained from the pyrolyzed scrap tyre by using both aqueous and Aloe vera gel as semi-aqueous/semi-organic electrolyte. The test results are obtained in the laboratory to ascertain the characteristics of developed supercapacitor in terms of capacitance, internal resistance and peak current. The obtained results are superior as compare to Vulcan XC-72R with trade-off between peak discharge current and other parameters. New carbon material obtained from scrap tyres is cost effective when used along with Aloe vera gel as an electrolyte. Use of scrap tyre carbon as electrode material and Aloe vera gel as naturally available material for electrolyte is an innovation of the presented work.